Long term complications of ventilation tube insertion in children with otitis media with effusion - Djordjević, Vladimir Živorad; Bukurov, Bojana; Arsović, Nenad; Ješić, Snežana; Milovanović, Jovica; Nešić, Vladimir (Vojnosanitetski pregled, 2014)
Background/Aim. Otitis media with effusion (OME) is characterized by the prolonged presence of fluid (longer than 12 weeks) of different viscosity in the middle ear, without perforation of the eardrum or signs of acute inflammation. The conservative treatment does not always provide satisfactory recovery, so surgical treatment may be unavoidable. The aim of the study was to determine the incidence, type and frequency of complications caused by ventilation tube insertion as a part of treatment for OME in children, and specifically, to evaluate the evolution of these changes over the extended period of time. Methods. During a 5-year period (1986–1991), 84 children with chronic bilateral OME, aged from 6 months to 12 years, were enrolled in the study and treated with ventilation tube insertion. All the patients were periodically checked every 6 months over a 3–8 year period following the intervention (otomicroscopic examination, audiometry, tympanometry), and reexamined in 2013 (22–27 years after the primary surgical intervention). Results. The complications observed in this study (51%) were atrophic scarring of the tympanic membrane, myringo- and tympanosclerosis, retraction of the eardrum, persistent perforations, granulation tissue formations, development of chronic otitis and sensorineural hearing loss. Conclusion. The incidence of complications after ventilation tube insertion was 51% in this study. Atrophic scars and myringosclerosis were the most prominent complications. Despite high complications rate ventilation tube insertion still remains the treatment of choice in children with otitis media with effusion.